IPO Behavior in GCC Countries : Goody-Two Shoes or Bad-to-the-Bone? (IMF Working Papers; Working Paper, 2007)
This paper documents the phenomenon of underpricing initial public offerings (IPOs) for 47 firms that went public between 2001 and 2006 in the equity markets of the six Gulf Cooperation Council (GCC) countries. The average initial abnormal returns of 290 percent exceed those found in the existing literature for both developed and emerging markets IPOs. Although the IPOs' returns over the one-year horizon beat the market index benchmark, they present negative abnormal returns once initial returns are excluded, which is consistent with findings in other industrial and emerging markets. The empirical models reject the hypothesis that the IPOs' performance is driven by the common independent variables employed in the literature. On the contrary, in the case of the GCC, country- and industry-specific characteristics, in addition to the timing of the offers, play key roles in explaining the abnormal returns of IPOs. This paper's empirical findings support the hypothesis that investors initially tend to be over-optimistic about the performance of IPOs, but grow more pessimistic over time.